1995
DOI: 10.1111/j.1365-2958.1995.tb02267.x
|View full text |Cite
|
Sign up to set email alerts
|

ComC is required for the processing and translocation of ComGC, a pilin‐like competence protein of Bacillus subtilis

Abstract: ComGC is a cell surface-localized protein required for DNA binding during transformation in Bacillus subtilis. It resembles type IV prepilins in its N-terminal domain, particularly in the amino acid sequence surrounding the processing cleavage sites of these proteins. ComC is another protein required for DNA binding, which resembles the processing proteases that cleave type IV prepilins. We show here that ComGC is processed in competent cells and that this processing requires ComC. We also demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 32 publications
3
73
0
1
Order By: Relevance
“…We have shown previously that ComGC is processed by a pathway that is dependent on ComC (Chung and Dubnau, 1994). This observation has now been extended to ComGD, GE and GG (Fig.…”
Section: Localization Of Comgasupporting
confidence: 63%
See 4 more Smart Citations
“…We have shown previously that ComGC is processed by a pathway that is dependent on ComC (Chung and Dubnau, 1994). This observation has now been extended to ComGD, GE and GG (Fig.…”
Section: Localization Of Comgasupporting
confidence: 63%
“…Processing of pre-ComGC is followed by the translocation of the mature protein from its position as an integral membrane protein to a new location outside the cell membrane, although roughly half of the processed molecules remain as NaOH-insoluble membrane-spanning proteins (Chung and Dubnau, 1994). In the present study, we have observed that a previously undetected fraction of the mature protein is released when the cell wall is hydrolysed by treatment with lysozyme or mutanolysin in an osmoprotective medium.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations